Development of Learning Video Reflection Using Palembang Songket Context to Determine Students' Mathematical Reasoning - Jariyah, Ainun; Putri, Ratu Ilma Indra; Zulkardi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Students must have strong mathematical thinking skills after seeing reflection learning videos with a Palembang songket context. The goal is to create a realistic and practical learning film, and to understand the potential impact of students' mathematical reasoning abilities on Palembang songket setting through reflection material. This study employs PMRI and a collaborative learning approach. Design research is used to conduct development studies. While the subjects were 28 kids from class IX.B with varying capacities. Data were gathered by observation, exams, and interviews. Data analysis methods included observation, testing, and interviews. The learning video on reflection material using the context of Palembang songket is valid and practical, and students' mathematical reasoning skills have been classified as good with an average value of 65.81 following the implementation of learning using learning videos, with the most frequent indicator appearing as making conjectures and the least frequent indicator appearing as drawing conclusions. The difficulty with this study is the absence of compelling learning films offered. Students can improve their mathematical reasoning skills by watching learning films about reflection material set in the setting of Palembang Songket.